Global Landscape of m6A Methylation of Differently Expressed Genes in Muscle Tissue of Liaoyu White Cattle and Simmental Cattle - Dang, Yunlong; Dong, Qiao; Wu, Bowei; Yang, Shuhua; Sun, Jiaming; Cui, Gengyuan; Xu, Weixiang; Zhao, Meiling; Zhang, Yunxuan; Li, Peng; Li, Lin (Frontiers in Cell and Developmental Biology, 2022)
Liaoyu white cattle is a local breed in Liaoning Province, China. It has the advantages of large body, large meat production, good meat quality and strong stress resistance. N6 methyladenosine (m6A) is a methylation modification of N6 position of RNA adenine, which is an important modification mechanism affecting physiological phenomena. However, there are few reports on m6A in beef cattle. In this study, we used the longissimus dorsi muscle of Liaoyu white cattle (LYWC) and Simmental cattle (SIMC) for m6A-seq and RNA-seq high-throughput sequencing, and identified the key genes involved in muscle growth and m6A modification development by bioinformatics analysis. There were 31532 m6A peaks in the whole genome of Liaoyu white cattle and 47217 m6A peaks in the whole genome of Simmental cattle. Compared with Simmental cattle group, Liaoyu white cattle group had 17351 differentially expressed genes: 10697 genes were up-regulated, 6654 genes were down regulated, 620 differentially expressed genes were significant, while 16731 differentially expressed genes were not significant. Among the 620 significantly differentially expressed genes, 295 genes were up-regulated and 325 genes were down regulated. In order to explore the relationship between m6A and mRNA expression in the muscles of Liaoyu white cattle and Simmental cattle, the combined analysis of MeRIP-seq and RNA-seq revealed that 316 genes were m6A modified with mRNA expression. To identify differentially methylated genes related to muscle growth, four related genes were selected for quantitative verification in LYWC and SIM. GO enrichment and KEGG analysis showed that the differentially expressed genes modified by m6A are mainly involved in skeletal muscle contraction, steroid biosynthesis process, redox process, PPAR pathway and fatty acid metabolism, and galactose metabolism. These results provide a theoretical basis for further research on the role of m6A in muscle growth and development.